Inhibitory proteaz w surowicach pacjentów z cukrzycową retinopatią prostą - Skopiński, Piotr; Duda-Król, Barbara; Lipińska, Anna; Sommer, Ewa; Borowska, Adamina; Filewska, Małgorzata; Szaflik, Jerzy; Skopińska-Różewska, Ewa; Struzik, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Diabetes is associated with a hypercoagulable state. Eighty percent of patients with diabetes mellitus die due to various thrombotic vascular complications. Disorder of coagulation and fibrynolysis is associated with diabetic retinopathy and nephropathy (1, 2, 3). Angiogenesis requires degradation of vascular basement membrane prior to migration and proliferation of endothelial cells. Various serine proteases play important role in this process. The homeostatic system is also the source of endogenous inhibitors of angiogenesis (4, 5, 6,). Human serum contains various factors able to induce or suppress formation of new blood vessels. The aim of the present study was to evaluate the activity of some angiogenesis inhibitors, anti-proteases, anti-thrombin III, a1 anti-trypsin and a2 anti- plasmin in sera of patients with diabetes mellitus type 1 and 2 and non-proliferative retinopathy, and to correlate this activity to total angiogenic potential of these sera, measured by mice cutaneous test. Sera of 22 persons with DM1, aged 33-70 years, 35 persons with DM2, aged 37- 79 years, and 51 healthy people, aged 22-80 years (as control group) were studied. Direct serum-induced cutaneous angiogenesis test in mice (SIA) was applied (7, 8). Berichrom (ade Behring) tests and immunoturbidimetric method were used for evaluation of antiproteases activity. Angiogenic activity of DM1 patients sera was statistically lower than this parameter in DM2 patients and in control group. Levels of anti-proteases were similar in DM1, DM2 and control group, with one exception: anti-thrombin level was lower in DM2 patients' sera than this in the control group. Analysis of correlation revealed important difference in behaviour of DM1 sera, as compared to other groups. Significant negative correlation was observed between angiogenic activity and anti-thrombin, as well as anti-trypsin level of DM1 patients' sera. On the other hand, correlation analysis performed for the sera of control group revealed significant positive correlation between their angiogenic activity and anti-thrombin level. No other correlations were found.